Modern Methods Of Treatment Of Chronic Generalized Periodontitis (Texas Journal of Medical Science, 2026)
Chronic generalized periodontitis (CGP) is one of the most common inflammatory-destructive periodontal diseases, leading to progressive loss of supporting tooth tissues and their premature loss. Modern treatment methods for CGP are aimed at eliminating microbial biofilm, controlling the inflammatory process, and restoring periodontal tissues using both conservative and surgical approaches. The aim of the study was to evaluate the effectiveness of complex treatment of chronic generalized periodontitis using modern ultrasonic, antimicrobial, and regenerative methods. It was established that the combined approach provides a statistically significant reduction in inflammatory indices, improvement of periodontal clinical status, and stabilization of the pathological process.